Text, Teachers and Tradition: A Survey of Granny Granny Please Comb My Hair - Manwal, Kalpana (THE PRIMARY TEACHER, 2019)
The New Education Policy (NEP) 2020 reiterates the role of parents and the community in the holistic development of a child. It emphasises the active involvement of parents in the scholastic and co-scholastic milestones of a child. Through the lens of the NEP, the existing language textbooks cover several aspects but are more focused on the traditionally prevalent family dynamics and structures. The space and scope for the extension of conversation is limited. This paper aims to cover the perspectives of primary teachers on the portrayal of family dynamics in texts and the portrayal of families, especially grandparents, in textbooks and the relevance learners can find in such texts, through the example of a poem Granny, Granny, Please Comb My Hair.